Post-Ugi Cyclization for the Construction of Diverse Heterocyclic Compounds: Recent Updates - Bariwal, Jitender; Kaur, Rupinder; Voskressensky, Leonid G.; Van der Eycken, Erik V. (Frontiers in Chemistry, 2018)
Multicomponent reactions (MCRs) have proved as a valuable tool for organic and medicinal chemist because of their ability to introduce a large degree of chemical diversity in the product in a single step and with high atom economy. One of the dominant MCRs is the Ugi reaction, which involves the condensation of an aldehyde (or ketone), an amine, an isonitrile, and a carboxylic acid to afford an α-acylamino carboxamide adduct. The desired Ugi-adducts may be constructed by careful selection of the building blocks, opening the door for desired post-Ugi modifications. In recent times, the post-Ugi transformation has proved an important synthetic protocol to provide a variety of heterocyclic compounds with diverse biological properties. In this review, we have discussed the significant advancements reported in the recent literature with the emphasis to highlight the concepts and synthetic applications of the derived products along with critical mechanistic aspects.